Music and consciousness philosophical, psychological, and cultural perspectives - Clarke, David (David Ian); Clarke, Eric F. (Oxford : Oxford University Press, 2011)
Consciousness poses major challenges to human understanding. This book considers whether music might afford some special source of insight into consciousness, and how issues of consciousness might in turn shape our understanding of music.
Description based on print version record.
Includes index.
Keywords: Music -- Psychological aspects; Music -- Philosophy and aesthetics; Consciousness